EFFECTS OF ROAD TRANSPORTATION ON SOCIO-ECONOMIC DEVELOPMENT OF RURAL COMMUNITIES IN KANO NORTH SENATORIAL DISTRICT, KANO STATE, NIGERIA - Altine, R.U.; Hamidu, A.K.; Usman, B.; Yusuf, A.; Bello, A.M.; Gwadabe, M. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
The study examined the effects of road transportation on socio-economic development of rural communities in Kano North Senatorial District, Kano State, Nigeria. Multistage sampling procedure was used to select 400 respondents. Data were collected using structured questionnaire and analysed using both descriptive and inferential statistics. The finding revealed that, road transport has effect on social and economic development. Economic activities connected to road had a positive coefficient (0.350341) and was statistically significant at 5% level. This indicates that a unit increase in economic activities connected to road would lead to increase in economic development by35%. Access to road in reducing transportation cost had a positive coefficient (0.1807951) and was statistically significant at 5% level. This indicates that a unit increase in access to road in reducing transportation cost would lead to increase in social development by 18%. It concluded that government should provide access to more roads that will help in providing more works to ease life. It was recommended that, there was a very serious high cost of transportation, high transport costs can take up a significant portion of a household’s budget affecting spending on other essential needs like food, education and healthcare.